A model for electronic commerce success - Quaddus, Mohammed; Achjari, Didi (Elsevier Science, 2005)
This paper attempts to develop a framework for electronic commerce (e-commerce) success. Key factors impacting e-commerce are identified from a detailed literature review. These factors are then differentiated according to their contribution to the success of e-commerce and according to the locus of impact. The final model is then cast in a structural equation modeling framework comprising four exogenous variables (internal driver, internal impediment, external driver and external impediment) and one endogenous variable (e-commerce success) with 24 observed variables. Data are collected via a questionnaire-based survey from large Australian companies. The study results suggest that increased benefits (both internal and external) from the use of e-commerce significantly predict the perceived and/or expected success of e-commerce. However, lowering of impediments (internal and external) does not significantly affect the success of e-commerce.